Loyalitas nasabah pada Bank Syariah Indonesia: Dampak relationship marketing dan mobile banking dengan switching barrier sebagai variabel moderating - Sutomo, Dudi Agus; Rofiuddin, Mohammad (Nur Science Institute, 2022)
This research aims to determine the effect of relationship marketing and mobile banking on customer loyalty at Bank Syariah Indonesia, with switching barriers as a moderating variable. The sample used in this research was 100 customers, with a sampling technique using a questionnaire. The analytical method used is a moderated regression analysis (MRA). The results show that the relationship marketing variable positively affects loyalty. Mobile banking harms loyalty. The results of the MRA analysis show that the switching barrier variable can moderate the influence of relationship marketing and mobile banking variables on customer loyalty.